There is no age limit for methadone: a retrospective cohort study - Wiesbeck Gerhard A; Vogel Marc; Dürsteler-MacFarland Kenneth M; Petitjean Sylvie A (BMC, 2011)
Abstract Background Data from the US indicates that methadone-maintained populations are aging, with an increase of patients aged 50 or older. Data from European methadone populations is sparse. This retrospective cohort study sought to evaluate the age trends and related developments in the methadone population of Basel-City, Switzerland. Methods The study included methadone patients between April 1, 1995 and March 31, 2003. Anonymized data was taken from the methadone register of Basel-City. For analysis of age distributions, patient samples were split into four age categories from '20-29 years' to '50 years and over'. Cross-sectional comparisons were performed using patient samples of 1996 and 2003. Results Analysis showed a significant increase in older patients between 1996 and 2003 (p < 0.001). During that period, the percentage of patients aged 50 and over rose almost tenfold, while the proportion of patients aged under 30 dropped significantly from 52.8% to 12.3%. The average methadone dose (p < 0.001) and the 1-year retention rate (p < 0.001) also increased significantly. Conclusions Findings point to clear trends in aging of methadone patients in Basel-City which are comparable, although less pronounced, to developments among US methadone populations. Many unanswered questions on medical, psychosocial and health economic consequences remain as the needs of older patients have not yet been evaluated extensively. However, older methadone patients, just as any other patients, should be accorded treatment appropriate to their medical condition and needs. Particular attention should be paid to adequate solutions for persons in need of care.